Tahap Kemahiran Employability Pelajar Kejuruteraan dari Perspektif Majikan (Sains Humanika, 2013)
Employers now require employees who mastered the technical and employability skills. Unfortunately employability skills acquired by does not meet the criteria education institution graduates by employers. This study aims to evaluate the level of employability skills on engineering students at higher education institutions from the perspective of employers. The descriptive study used quantitative approach involve a total of 171 respondents which is the engineering employers who were provided placement for industrial training to students of technical institutions. The instrument used in this study were adapted from the instruments of Modul Kemahiran Insaniah Kementerian Pengajian Tinggi Malaysia, Secretary’s Commission on Achieving Necessary Skill (SCANS) Amerika, Malaysian Qualification Framework (MQF), MyGSI and IKGPP and severel models from previous studies. The variables of this study are communication skills, spiritual skills, teamwork, leadership, lifelong learning and information management, critical thinking and problem solving, entrepreneurship, ethics and morality, technology skills, and social skills. Data collected were analyzed using descriptive and inferential analysis statistics. The results showed that the level of employability skills among engineering students from the employer's perspective is moderately high. The results also showed that there are no significant differences between student’s employability skills that are assessed against the nature of the industry, the position and the employer experience, and the location of the industry.
Keywords: Employers; industry; technical institutions; engineering; employability skills